Analysis of the Challenges and Dilemmas in the Categorization of Economic, Social and Cultural Rights - OGUNBANJO, Bimbo (Al-Adab Journal, 2024)
This paper discusses the limitations associated with the basic classification of human rights into several categories. The topic of whether international trends have an impact on the State's view of the significance of implementing rights through the acceptance of individual complaint procedures is a complex one. Starting with an acknowledgment of the infinite extent of the issue, this paper displays a belief in the fallacious conceptions of differences in human rights. It investigates and assesses the institutional contribution to the advancement of human rights through a chronological analysis of historical processes that give rise to changes in the 20th century. To address this particular distinction, this paper looks to the 1993 Vienna Declaration and Program of Action and the new Optional Protocol for validation and endorsement. By highlighting many similarities in the language and nature of State responsibilities, it challenges the reader to consider whether non-justiciability provides a basis in the first place. The purpose of this paper is to investigate the function of dispute resolution mechanisms during the implementation phase. From a practical standpoint, it compels the reader to contemplate if the committee procedures outlined in international conventions serve just as symbolic representations of non-cooperation by States or are put into effect. This paper ultimately presents the reader with some thought-provoking material in the shape of the dichotomy between enforcement and justiciability.